Establishment of a World Food Preservation Center: Concept, Need and Opportunity - Wilson , Charles L (Journal of Postharvest Technology, 2024)
The United Nations estimates that our global population will increase by one quarter and grow to 9.6 billion by 2050 (Anon, 2013). Most of this growth will occur in urban areas and emerging economies in Asia, Latin America, sub Saharan Africa. How we feed this ballooning population will become one of the most challenging problems of our time. Awareness of this urgent issue is slow in developing in the industrialized world where food is generally abundant. Yet, the primary responsibility for solving this problem rests with developed countries.